Evaluation of cowpea cultivars under intercropping system with annual cotton - Beltrão, Napoleão E. de M.; Santana, João Cecílio F. de; Crisóstomo, João R.; Araújo, João P. P. de; Sousa, Roberto P. de (Pesquisa Agropecuaria Brasileira, 2014)
With the objective of evaluating cowpea (Vigna unguiculata (L.) Walp.) cultivars regarding their agronomic characteristics, seed quality and levels of competition with annual cotton (Gossypium hirsutum L., r. latifolium) in an intercropping production system, an experiment was carried out at Gurinhém, PB, Brazil, in 1983. Twelve cultivars of cowpea with different growth and fruiting characteristics were used in this experiment. Two rows of cowpea were planted between rows of cotton. The cowpeas were planted 35 cm (leaving five plants per meter of row) from the adjoining cotton rows with a 30 cm spacing between the two rows of cowpea. Cotton was grown in rows 1,0 m x 0,20 m apart. Only three cultivars of cowpea (Epace 6, 40 days and CNC x 105-5E) did not significantly reduce the yield of the annual cotton indicating that these cowpea cultivars are well adapted to an intercropping system with annual cotton. The twelve cultivars of cowpeas showed no statistical difference in yield grain and had an average of 489 kg/ha.